2018
DOI: 10.1136/bmjopen-2018-022184
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multiple lifestyle risk factors and their link to mental health in the German adult population: a cross-sectional study

Abstract: ObjectivesLifestyle risk factors, such as drinking or unhealthy diet, can expotentiate detrimental health effects. Therefore, it is important to investigate multiple lifestyle risk factors instead of single ones. The study aims at: (1) identifying patterns of lifestyle risk factors within the adult general population in Germany and (2) examining associations between the extracted patterns and external factors.DesignCross-sectional study.SettingGeneral German adult population (aged 18–64 years).ParticipantsPart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…Specifically, individuals in the ''cumulate harmful habits'' group reported the highest prevalence of certain behaviors concurrently. This is coherent with the previous literature (Atzendorf et al, 2018;Kino, Bernabe & Sabbah, 2017;Noble et al, 2015), suggesting that there may be a common underlying cause of HRBs. Additionally, we also observed an association between sleep problems and risky behaviors.…”
Section: Clustering Of Health Risk Behaviorssupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, individuals in the ''cumulate harmful habits'' group reported the highest prevalence of certain behaviors concurrently. This is coherent with the previous literature (Atzendorf et al, 2018;Kino, Bernabe & Sabbah, 2017;Noble et al, 2015), suggesting that there may be a common underlying cause of HRBs. Additionally, we also observed an association between sleep problems and risky behaviors.…”
Section: Clustering Of Health Risk Behaviorssupporting
confidence: 93%
“…The results reinforce the idea that health behaviors tend to cluster at the upper and lower ends of the spectrum (Noble et al, 2015). However, both current and previous findings revealed that even individuals in the ''healthy'' class exhibited low physical activity (Atzendorf et al, 2018;De Mello et al, 2019). It reflects the difficulties for general adults in self-regulatory behaviors like physical activity, and highlights the need to increase health services concerning health-promoting behaviors.…”
Section: Clustering Of Health Risk Behaviorssupporting
confidence: 87%
See 1 more Smart Citation
“…In recent years, some research has assessed how a range of lifestyle factors may influence our mental wellbeing, with several cross-sectional studies, for example [20][21][22][23] revealing that other elements such as a healthy diet, adequate duration of sleep, outdoor or sunlight exposure, alcohol limitation, and smoking avoidance are beneficial behaviours which relate to general mental health and mood. This data is compelling and stands to reason due to the well-documented effects that nutrition, sleep, physical activity, sunlight and air quality, and harmful recreational substances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Within the early intervention paradigm in psychiatry (72), special attention is paid to modifiable risk factors (73,74), i.e., factors that can be manipulated by early specific and preventive interventions moderating their longitudinal role in contributing to the risk of psychosis and schizophrenia (75). With respect to intergenerational liability, one of the most important modifiable risk factors includes parenting, whose quality is strongly correlated with severity and chronicity of mother mental illness (76,77), including SSD (78)(79)(80)(81).…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%